Distancing the Present Self from the past and the Future: Psychological Distance in Anxiety and Depression. Issue 7 (July 2017) - Rinaldi, Luca; Locati, Francesca; Parolin, Laura; Girelli, Luisa
Humans show a systematic tendency to perceive the future as psychologically closer than the past. Based on the clinical hypothesis that anxiety would be associated more with future threat life events, whereas depression with past loss events, here we explored whether people with anxiety- and depression-related personality traits perceive differently the psychological distance of temporal events. Results showed that the common tendency to perceive the future as psychologically closer than the past is exaggerated in individuals with anxiety-related personality traits, whereas this asymmetry drastically shrinks in individuals with depression-related personality traits. Beyond substantiating the hypothesis that the past and the future are differently faced by people with depression- and anxiety-related personality traits, the present findings suggest that temporal orientation of one's self may be greatly altered in anxiety and depression.